Kolaborasi Mikrobiologi Pangan dalam Pendidikan Biologi untuk Mendukung Implementasi Sustainable Development Goals (SDGs) - Setyaningrum, Yahmi (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Collaboration between food microbiology and biology education is an effort to support the Sustainable Development Goals (SDGs) in food security (SDG 2), good health (SDG 3) and quality education (SDG 4). Collaboration aims to improve food safety, microbiology quality, and its impact on human health. Problem-Based Learning and Project-Based Learning strategies, supported by information technology (IT) are efforts to support the SDGs. The use of e-learning platforms, laboratory practices, and interactive learning applications allow students to access the latest materials, data, and research in food and nutrition microbiology flexibly and effectively. This learning strategy, collaboration between microbiology, food, and nutrition in biology education can improve the quality of learning and produce graduates who are ready to contribute to achieving the SDGs, especially in the fields of nutrition, health and food. Keywords: Nutritions, Food Microbiology, Biology Educations, SDGs